Features of Business Relocation in Wartime: Evidence from Ukrainian Entrepreneurs - Larysa Yakymova; Jakimova L.; Лариса Якимова (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Fighting and the threat of occupation are forcing businesses to move to safer regions. This study aims to identify the decision-making determinants, challenges and strategies of relocation and recovery in a new location related to operations and team. For this purpose, semi-structured and narrative interviews published on Internet resources with representatives of enterprises relocated to safer regions of Ukraine and local authorities were analyzed. The final sample is 80 enterprises. The study found that the main criteria for choosing a new location (after safety), are convenient logistics and the availability of a relevant site for locating production. When preparing for a move and during the move, the main problems are danger to life, organizing transport and dismantling/loading equipment. From a moral and psychological point of view, the main issue is to persuade employees to relocate. As a result, the biggest challenge when restarting a business in a new location was creating a team in the absence of local workers with relevant skills. As for business strategies in the new conditions, the main trend is this: large companies are introducing innovative approaches to organizing production and management, medium and small enterprises are changing their product range or activity profile, adapting to the needs of wartime and/or the host region. The study revealed the positive effects of relocating businesses on the economy and infrastructure of host communities. Moreover, there is reason to argue that the relocation of a large number of industrial enterprises to the non-industrial western regions of Ukraine due to the war is changing the economic map of Ukraine. After the war, the Ukrainian entrepreneur plans to restore his native region, while the enterprise opened in a new location will continue to operate as a division. These findings should be taken into account by the government when planning post-war recovery. Additionally, in the current climate of global uncertainty about the progress of the war, governments and businesses must develop contingency plans that include nudge policies for their employees.

A katonai hadműveletek és a megszállás veszélye arra kényszeríti a vállalkozásokat, hogy biztonságosabb régiókba költözzenek. E tanulmány célja, hogy meghatározza a döntési meghatározó tényezőket, kihívásokat és stratégiákat az áttelepülés és a helyreállítás új helyre történő áthelyezésével kapcsolatban a műveletekkel és a csapattal kapcsolatban. E célból félig strukturált és narratív interjúkat elemeztek az Ukrajna biztonságosabb régióiba áttelepült vállalkozások képviselőivel és az interneten közzétett helyi hatóságokkal. A végső minta 80 vállalkozásból állt. A felmérésből kiderült, hogy az új helyszín kiválasztásának fő szempontjai (a biztonság után) a kényelmes logisztika és a termeléshez megfelelő helyszín rendelkezésre állása. Az áthelyezési folyamat során a legnagyobb kihívásként az életveszélyes helyzeteket, a szállítási intézkedéseket és a berendezések leszerelését/elrakodását jelölték meg. Erkölcsi és pszichológiai szempontból a fő problémát az jelentette, hogy a munkavállalókat meg kellett győzni a költözésről. Ennek eredményeképpen a vállalkozás új helyen történő újraindítása során a legnagyobb kihívást a megfelelő képesítéssel rendelkező helyi alkalmazottak hiányában a csapatépítés jelentette. Az új környezetben az üzleti stratégiát illetően a fő tendencia a következő: a nagyvállalatok innovatív megközelítéseket vezetnek be a termelés és az irányítás terén, míg a közép- és kisvállalkozások a háborús idők és/vagy a fogadó régió igényeihez igazodva megváltoztatják termékkínálatukat vagy profiljukat. A tanulmány megállapította, hogy a vállalkozások áthelyezése pozitív hatással van a fogadó közösségek gazdaságára és infrastruktúrájára. Továbbá okkal feltételezhető, hogy a háború következtében jelentős számú ipari vállalkozásnak Ukrajna nem ipari jellegű nyugati régióiba történő áttelepülése megváltoztatja Ukrajna gazdasági térképét. A háború után az ukrán vállalkozók azt tervezik, hogy újjáépítik szülőföldjüket, és az új helyen megnyitott vállalkozás egységként működik tovább. Ezeket a megállapításokat a kormánynak figyelembe kell vennie a háború utáni helyreállítás tervezésénél. Ezenkívül a háború lefolyásával kapcsolatos jelenlegi globális bizonytalansági környezetben a kormányoknak és a vállalkozásoknak olyan vészhelyzeti terveket kell kidolgozniuk, amelyek tartalmazzák a munkavállalók számára a ösztönzési politika leírását.

Резюме. Бойові дії та загроза окупації змушують бізнес переїжджати до більш безпечних регіонів. Це дослідження має на меті виявити детермінанти прийняття рішень, виклики і стратегії релокації та відновлення у новій локації, які пов’язані з операціями і командою. Для цього проаналізовано, оприлюднені на Інтернет-ресурсах напівструктуровані та наративні інтерв’ю з представниками підприємств, релокованих у більш безпечні регіони України, та місцевої влади. Фінальна вибірка – 80 підприємств. Дослідження показало, що основними критеріями вибору нової локації (після безпеки) є зручна логістика і наявність відповідного майданчика для розміщення виробництва. Найбільшими викликами під час переїзду визнано небезпеку для життя, організацію транспорту та демонтаж/завантаження обладнання.. З морально-психологічного погляду головна проблема полягала у переконанні працівників переїхати. Як наслідок, найбільшим викликом під час відновлення бізнесу у новій локації стало створення команди за відсутності місцевих працівників з відповідною кваліфікацією. Що стосується бізнес-стратегії у нових умовах, то основна тенденція така: великі компанії впроваджують інноваційні підходи до організації виробництва та управління, середні та малі підприємства змінюють асортимент або профіль діяльності, адаптуючись до потреб воєнного часу та/або приймаючого регіону. Дослідження виявило позитивний вплив релокації підприємств на економіку та інфраструктуру приймаючих громад. Більше того, є підстави стверджувати, що переміщення внаслідок війни значної кількості промислових підприємств у непромислові західні регіони України змінює економічну мапу України. Після війни український підприємець планує відновлювати рідний регіон, а відкрите у новій локації підприємство продовжить працювати як підрозділ. Ці висновки мають враховуватися урядом під час планування повоєнного відновлення. Крім того, у поточних умовах глобальної невизначеності щодо перебігу війни уряди та підприємства мають розробити плани дій на випадок екстрених ситуацій, які б містили опис політики підштовхування щодо своїх співробітників.
Особливості релокації бізнесу у воєнний час: досвід українських підприємців
Az üzletáthelyezés sajátosságai háborús időkben: az ukrán vállalkozók tapasztalatai
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/5
Keywords: business relocation; full-scale war; safety; strategy; team